‘Do I even belong?' Interrogating Afro-diasporic navigation of identity, race and space in the search for belonging - Moragia, Anita Mwango (Centre for Film and Media Studies, 2020)
The departure point for this creative project is based on my experience as an African living in diaspora. While I felt many things during my time ‘away' from the African continent, one constant was always this feeling of unbelonging, and this need to find belonging. As such, this project centers around the theme ‘finding belonging in diaspora'. Growing up in Kenya, I had never really come to terms with the politics of my Kenyanness not to mention my blackness. I had simply just been me. While in Kenya, the only real identifiers I had to contend with that carried heavy politics were my gender and my tribal affiliation. After leaving Kenya and arriving in Canada for school at the age of 16, for the first time in my life I felt black and I felt African. Both identities I felt did not belong in this Canadian space. Over the course of 9 years, I lived in both Canada and London and neither ever warmed me like home. In most, if not all the predominantly white spaces I frequented, I always felt too little of something and too much of something else. As such,, I found myself intentionally and unintentionally drawn to those like me, in colour, in language, and culture. It is only today I have realised that those intentional and unintentional unions I formed were a result of my search for belonging, which I came to find is common in the diaspora experience. Ann Hua, a black diaspora scholar, defines diaspora as a community of people who have been dispersed from their homeland to other locations because of genocide, slavery, migration, and war (Hua, 2013; 31). It's important to note that for many, induction into the Afro-diaspora is involuntary. As Hua notes, political unrest, genocide, war, and slavery has forced many to leave their homes and either seek asylum or become indentured laborers elsewhere. We have seen this throughout the eras, from the 15th-century trans-Atlantic slave trade, capturing of Africans, transporting them to the Americas and coercing them into slavery (Gates Jr., 2017), to the 20th-century dispersion of Rwandese nationals fleeing genocide§ (Guichaoua, André & Webster, Don E. 2015). The identity of diaspora comes in both anticipated and unanticipated ways. Fortunately, my induction into the Afro-diasporic community was a voluntary one and the bulk of this project interacts with voluntary Afro-diasporic migrants. During my time in Canada and London, I met many members of the Afro-diasporic community who ended up in these countries in a variety of different ways and for a variety of different reasons. The theme of ‘finding belonging' was omnipresent among my fellow Afro-diasporic community members and it would manifest itself in various ways. For instance, wanting to go to African restaurants to feel more ‘at-home', or wanting to visit African night clubs to listen to more music from ‘home'. Interestingly, I also began to see that this journey towards ‘finding belonging' also manifested in Afro-diasporic communities rejecting assimilation into their new societies and creating spaces of resistance, through organising protests or hosting discussions that centred around issues of race.